2016
DOI: 10.1371/journal.pone.0153988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Cotton Subtilase Gene GbSBT1 in Response to Extracellular Stimulations and Its Role in Verticillium Resistance

Abstract: Verticillium wilt is a disastrous vascular disease in plants caused by Verticillium dahliae. Verticillium pathogens secrete various disease-causing effectors in cotton. This study identified a subtilase gene GbSBT1 from Gossypium babardense and investigated the roles against V. dahliae infection. GbSBT1 gene expression is responsive to V. dahliae defense signals, jasmonic acid, and ethylene treatments. Moreover, the GbSBT1 protein is mainly localized in the cell membrane and moves into the cytoplasm following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…The corresponding GbSBT1 protein showed to be mainly localized at the cell membrane and moves to the cytoplasm following treatment with jasmonic acid and ethylene, which supports the hypothesis of some grapevine subtilases are located near the place where occurs the plant-pathogen interaction. Moreover, Duan and co-workers, observed a reduction of the tolerance of a cotton resistant genotype, when the GbSBT1 gene was silenced, and an activation of the expression levels of defense-related genes (Duan et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The corresponding GbSBT1 protein showed to be mainly localized at the cell membrane and moves to the cytoplasm following treatment with jasmonic acid and ethylene, which supports the hypothesis of some grapevine subtilases are located near the place where occurs the plant-pathogen interaction. Moreover, Duan and co-workers, observed a reduction of the tolerance of a cotton resistant genotype, when the GbSBT1 gene was silenced, and an activation of the expression levels of defense-related genes (Duan et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Direct interaction with a pathogen effector was shown for GbSBT1 from cotton ( Gossypium barbadense ). The protease was shown to interact with a prohibitin (PHB)‐like effector protein which is secreted by Verticillium dahliae during infection (Duan et al ., ). Gain‐ and loss‐of‐function studies confirmed a role for GbSBT1 in Verticillium wilt resistance (Duan et al ., ).…”
Section: Physiological Roles Of Plant Sbtsmentioning
confidence: 97%
“…In the past year, several studies have highlighted the involvement of subtilases in plant resistance to pathogens. In cotton, a subtilase called GbSBT1 has been identified, characterized and related to Verticillium dahliae ‐induced resistance (Duan et al ., ). In this study, the authors observed that GbSBT1 knockdown reduces cotton defence against V. dahliae attack.…”
Section: Subtilases Involved In Plant Defencementioning
confidence: 97%